Juvenile dermatomyositis: common manifestations of a rare disease - Capela, Mariana; Reis, Joana; Soares, Diana; Ribeiro, Andreia; Pais, Isabel Pinto; Rodrigues, Lúcia Trindade (BIRTH AND GROWTH MEDICAL JOURNAL, 2020)
Juvenile dermatomyositis is an autoimmune systemic vasculopathy, mainly characterized by chronic inflammation of the striated muscle and skin. The authors report the case of a 15-year-old boy presenting with a four-month history of myalgia and proximal muscle weakness on the upper and lower limbs. These symptoms were associated with heliotrope palpebral exanthema, erythema in the dorsum of the hands, Gottron’s papules, erythematous and petechial rash on the extensor face of the thighs, and mild dysphagia for solids. Blood tests revealed an increase in muscle enzymes and electromyography showed changes suggestive of severe acute myopathy. Intravenous methylprednisolone was initiated, followed by a combination regimen of prednisolone and methotrexate. Progressive dysphagia, cutaneous abnormality, and muscular strength improvement were noted. With this case, the authors intend to raise awareness of a rare disease with an essentially clinical diagnosis, presenting in most cases with characteristic manifestations that should be recognised.